PENGEMBANGAN MEDIA PAPAN BALIK (FLIPCHART) UNTUK MENINGKATKAN KEMAMPUAN BACA ANAK BERKEBUTUHAN KHUSUS DENGAN HAMBATAN AUTIS DI SEKOLAH INKLUSI - Suchaimatul Lutfia; Setya Yuwana; Hendratno Hendratno (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2021)
This study aims to produce flipchart media products to improve the reading ability of children with special needs with autism in inclusive schools. Because education is the right of every child. Therefore, children with special needs with autism have the right to receive learning according to their conditions. This research method uses research and development methods with a 4-D cycle (define, design, develop and disseminate). The subjects of this study were 6 students with special needs with autism at SD Muhammadiyah, Tulangan sub-district Sidoarjo. The sample of 6 students was selected based on categories, 2 students with mild autism and reading difficulties, 2 students with moderate autism and reading difficulties and 2 students with severe reading difficulties. The results of the study are as follows: (1) the material from the flipchart media developed is declared very feasible with a percentage value of 85.5%. (2) the results of the percentage value of media flipchart get a value of 83.75% with a decent category. (3) the test of the effectiveness of the developed flipchart media obtained a percentage value of 83.33%, a significance value of 0.000 > 0.05 so that there was a significant difference between the pre-test and post-test. Through the n-gain test, the score was obtained 0.33 which means the effect of the application is categorized as 'medium'. It can be concluded that the flipchart media developed had a positive effect on the reading ability of students with special needs with autism at SD Muhammadiyah Tulangan Sidoarjo. Keywords: Reading Ability, Flipchart Media, Autistic Child, Inclusive School